Solidity Analysis of The Golkar Party in Jambi City in the 2024 Simultaneous Regional Head Elections - Ica Fitriani; Dimas Subekti; Ian Pasaribu; Hatta Abdi Muhammad (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
The 2024 Simultaneous Regional Head Elections constitute a critical test of intra-party cohesion in Indonesia’s increasingly competitive electoral landscape. This study examines the internal solidity of the Golongan Karya (Golkar) Party in Jambi City following internal conflict over the nomination of mayoral candidates. The dispute emerged from divergent preferences between the City Regional Leadership Council (DPD II), which endorsed internal cadres, and the Provincial and Central leadership (DPD I and DPP), which prioritized electability in selecting alternative candidates. Employing a qualitative case study design, this research draws on in-depth interviews with party officials, cadres, political observers, and academics, complemented by party documents and media reports. Data were analyzed using Miles and Huberman’s interactive model. The study offers a novel contribution by conceptualizing party solidity as adaptive rather than fully institutionalized, demonstrating how centralized authority, charismatic leadership, and cadre loyalty function as stabilizing mechanisms in the aftermath of internal conflict. The findings highlight the urgency of strengthening institutionalized decision-making processes to ensure sustainable party cohesion, thereby contributing to broader debates on party institutionalization and democratic consolidation in Indonesia.